Case Report: Curative effect of OA-PICA protected bypass in severe PICA-complicated vertebral artery stenosis treatment: Results in 3 cases - Zhao, Liming; Xue, Bingqian; Guo, Gaochao; Wu, Ruiyu; Gao, Tao; Liu, Yang; Sun, Yuxue; Hernesniemi, Juha; Andrade Barazarte, Hugo; Li, Tianxiao; Li, Chaoyue (Frontiers in Surgery, 2023)
Objectives We aimed to explore the results of OA-PICA-protected bypass grafting in patients with severe stenosis of the vertebral artery combined with PICA. Methods Three patients with vertebral artery stenosis involving the posterior inferior cerebellar artery, treated by the Department of Neurosurgery of Henan Provincial People's Hospital from January 2018 to December 2021, were retrospectively analyzed. All the patients underwent Occipital Artery–Posterior Inferior Cerebellar Artery (OA-PICA) bypass surgery followed by elective vertebral artery stenting. Intraoperative indocyanine green fluorescence angiography (ICGA) showed patency of the bridge-vessel anastomosis. Postoperatively, the ANSYS software was used to assess the flow pressure changes and vascular shear in combination with the reviewed DSA angiogram. CTA or DSA was reviewed 1–2 years postoperatively, and the prognosis was evaluated by the modified Rankin Scale (mRS) one year postoperatively. Results OA-PICA bypass surgery was completed in all patients, with intraoperative ICGA showing a patent bridge anastomosis, followed by stenting of the vertebral artery, and a review of the DSA angiogram. We also employed ANSYS software evaluation of the bypass vessel, which showed stable pressure and low turnover angle, suggesting a low rate of long-term occlusion of the vessel. All patients had no procedure-related complications during their hospitalization, and were followed up for a mean of 24 months postoperatively, with a good prognosis (mRS score of 1) at 1 year postoperatively. Conclusion OA-PICA-protected bypass grafting is an effective treatment for patients with severe stenosis of the vertebral artery combined with PICA.